As repercussões do esquematismo kantiano na Dialética do esclarecimento de Theodor Adorno e Max Horkheimer - Marcelo Antonio Rocha (2006)
This dissertation intends to present the relation between the Kantian transcendental schematism and the critique of the culture industry and anti-Semitism carried through by Theodor Adorno and Max Horkheimer in the Dialectic of Enlightenment. Regarding the critique of the culture industry, the aim is to point in which extend it appropriates the peoples capacity of schematism. In relation to anti-Semitism, to point in which extend the social and historical determination of our capacity to judge contributes, on one hand, to the heighten of anti-Semitism and, on the other hand, to the increasing intertwinement, in the enlightened western society, between the culture and barbarism.